Membongkar Makna di Balik Iklan Layanan Masyarakat tentang Makanan Ultra-Proses: Analisis Semiotika Roland Barthes - Aliyah, Sa'adatul; Dida, Susanne; Lusiana, Elnovani (SAWERIGADING, 2025)
This study aims to analyze the construction of the ultra-processed food narrative ideology in the BBC News Indonesia public service announcement on YouTube Shorts titled "Does Ultra-Processed Food Increase Early Death?". The method used is Roland Barthes' semiotic analysis, focusing on three layers of meaning: denotation, connotation, and myth of verbal and visual signs in advertising. Data collection techniques were carried out thru content analysis of advertisements and semi-structured interviews to uncover audience interpretations. Data analysis techniques used Barthes' semiotic framework to deconstruct the latent meanings behind visual and verbal representations. The research findings indicate that advertising not only conveys factual information but also constructs stigma against individuals based on their dietary choices and emphasizes individual responsibility rather than systemic-structural factors in maintaining health. The implications of this research emphasize the need for health communication that is more inclusive of social determinants and does not solely blame individuals AbstrakPenelitian ini bertujuan untuk menganalisis konstruksi ideologi narasi makanan ultra proses dalam iklan layanan masyarakat BBC News Indonesia di YouTube Shorts bertajuk "Apakah Makanan Ultra Proses Meningkatkan Kematian Dini?". Metode yang digunakan adalah analisis semiotika Roland Barthes dengan fokus pada tiga lapisan makna: denotasi, konotasi, dan mitos dari tanda verbal dan visual dalam iklan. Teknik pengumpulan data dilakukan melalui analisis konten iklan dan wawancara semi-terstruktur untuk mengungkap interpretasi audiens. Teknik analisis data menggunakan kerangka semiotika Barthes untuk membongkar makna laten di balik representasi visual dan verbal. Hasil penelitian menunjukkan bahwa iklan tidak hanya menyampaikan informasi faktual, tetapi membangun stigma terhadap individu berdasarkan pilihan pola makan dan menekankan tanggung jawab individual daripada faktor sistemik-struktural dalam menjaga kesehatan. Implikasi penelitian ini menekankan perlunya komunikasi kesehatan yang lebih inklusif terhadap determinan sosial dan tidak menyalahkan individu semata.